Citizens and saints politics and anti-politics in early British socialism - Claeys, Gregory 1951- (Cambridge University Press, 1989)
Citizens and Saints is a comprehensive study of the profound rupture in the language of reform and revolution which occurred with the rise of socialism. Focusing upon British Owenite socialism, Professor Claeys argues that two schools of political thinking emerged from the 'social' critique of contemporary political radicalism. One, largely identified with Owenite perfectibilism, aimed to transcend existing forms of democracy and to establish more harmonious, less divisive forms of rule. The other, apparently more democratic, aimed to extend popular control of political institutions to economic organisations. Both were sceptical of the 'political' analyses of socioeconomic deprivation proferred by existing radicalism. Such scepticism was to prove crucial to both liberal and socialist political thought, and Professor Claeys shows that such perennial questions as the intrinsically democratic (or otherwise) nature of Marxist socialism can only be understood by reference to the political and intellectual circumstances in which early socialist ideas emerged
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Owen, Robert / 1771-1858; Owen, Robert -- 1771-1858; Maine, Henry Sumner -- 1822-1888; Geschichte 1800-1900; Geschichte 1840-1970; Geschichte 1815-1860; Geschichte; Politik; Politische Wissenschaft; Socialism / Great Britain / 19th century; Political science / Great Britain / History / 19th century; Sozialismus; Recht; Frühsozialismus; Großbritannien; Great Britain / Politics and government / 19th century; Hochschulschrift